Genetic characteristics of mumps viruses isolated in Korea from 2007 to 2012. Issue 9 (11th May 2016) - Kim, Seung Tae; Kim, You‐Jin; Yang, Jeong‐Sun; Nam, Jeong‐Gu; Kim, Kisoon; Kim, Sung Soon; Kang, Hae Ji
Abstract : Mumps is a vaccine‐preventable viral disease. Despite vaccine coverage of >95%, the incidence of mumps has increased in Korea since 2007. This study aimed to genetically characterize mumps virus (MuV) strains that circulated in Korea between 2007 and 2012 to determine the factors underlying mumps outbreaks. MuV was isolated from 175 clinical specimens between 2007 and 2012 in Korea. Upon analysis of the SH gene in Korean mumps virus isolates, three different genotypes were identified: I, H, and F. The MuV genotypes I and H co‐circulated in Korea, and eight isolates of Korean genotype F were found within the same time period in 2008. An analysis of HN amino‐acid sequence data showed that Korean isolates had no changes in their glycosylation sites. At putative neutralizing epitope sites, the Jeryl‐Lynn strain showed 4–5 different amino acid sequences from those observed in Korean isolates. Korean isolates of genotypes I and H shared distinctive point mutations on putative neutralizing epitope positions in each genotype. This report describes the genetic characteristics of MuV strains circulating in Korea and provides information on endemic mumps infections. This information may be important to help prevent mumps and control outbreaks of mumps in Korea. J. Med. Virol. 88:1479–1486, 2016 . © 2016 Wiley Periodicals, Inc.